PENERAPAN MODEL NUMBEREAD HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR GETARAN SMP NEGERI 8 PONTIANAK - Sella Ardiani; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2020)
Abstrak This research was aimed to improve the students’ learning outcomes on the Vibration material using Numbered Head Together (NHT) learning model. This is pre-experimental research with a non-equivalent control group design, conducted at SMPN 8 Pontianak involving 28 students in class VIII C. The data were obtained using a test in the form of ten multiple-choice and five essays. Based on the Wilcoxon test using SPSS version 22, obtained Sig 2-tailed by 0.000 < 0.05; Thus, Ha was accepted. Therefore, it was concluded that there was a significant difference in the learning outcomes before and after the selected model was applied. The average scores obtained after applying NHT was 77.76, with the effect size by 1.86 (categorized high). In conclusion, the Numbered Head Together (NHT) learning model is effective to use in improving students’ learning outcomes in vibration material. Keywords: Vibration, Learning Outcomes, Numbered Head Together.